Dynamic analysis of high-speed traction elevator and traction car–rope time-varying system. (February 2019) - Zhang, Qing; Yang, Yu-hu; Hou, Tao; Zhang, Rui-jun
In this study, the compensating ropes and tension device on elevator vibration, as well as the car and hoisting ropes between the top of the car and traction wheel in a high-speed traction elevator lift system, were considered a system to analyze the effect of traction force. In addition, the vertical vibration of the system was used as the research object. The influence of hoisting ropes quality was measured, and a time-varying dynamic model with variable mass, damping, and stiffness for the car–hoisting rope system was constructed from the perspective of time-varying structural mechanics. Simultaneously, the ideal running state of the elevator, which is fitted by using the quintic polynomial, was utilized as input motion parameter. Then, a case study was conducted by using the fine integral method for the vertical vibration dynamic model of the car–hoisting rope system. Finally, the nonlinear vertical vibration response of the car–hoisting rope system during the operation of high-speed traction elevator was obtained. Results indicated that the influence of traction force, compensating ropes, and tension device on the vibration of the car–hoisting rope system when the elevator is in the upward process is greater than when the elevator is in the downward process. In addition, the low quality of the elevator car leads to the production of strong longitudinal vibration. The linear density of the hoisting ropes has a slight effect on the longitudinal vibration of elevator.